Searching for other images in education: report of an in-discipline between school and culture - Júnior, Wenceslao Machado de Oliveira; Oliveira, Tatiana Plens; Belleza, Eduardo de Oliveira (Revista Educação e Linguagens, 2020)
The article is a deployment of the lived experience in an undergraduate discipline in which was studied the images present in textbooks and their effect on the representational thought and trials with images were held in the search to cause erasures in the usual way they have in education. A route that culminated in a final challenge for the students: to create an educational activity inter-multi-trans-disciplinary with images, where they fell outside of the purely representational way. “An impossible activity” in the words of the students, which made clear the possibilities that are created at the images.